2001
DOI: 10.1103/physreve.64.051908
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties and efficiency of elastically coupled Brownian motors

Abstract: As models for biological molecular motors, Brownian motors have been studied recently by many workers, and their physical properties such as velocity, efficiency, and so on, have been investigated. They have also attracted much interest in an application to nanoscale technology. It is significant to study more complex systems, that is, coupled Brownian motors, in detail, since Brownian motors with a single particle have been mainly studied until now. In this paper, we consider Brownian motors coupled mutually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 10 publications
0
13
1
Order By: Relevance
“…The following are a few examples: Rigid rods of particles in overdamped, flashing ratchet systems display current reversals as a function of size and temperature [14]. Two harmonically coupled particles in an overdamped, flashing ratchet display higher center-of-mass velocity and energetic efficiency than a single particle [15]. Large collections of coupled particles in a flashing ratchet can undergo spontaneous oscillations [16], similar to the cooperative motion of muscle myosin.…”
Section: Introductionmentioning
confidence: 99%
“…The following are a few examples: Rigid rods of particles in overdamped, flashing ratchet systems display current reversals as a function of size and temperature [14]. Two harmonically coupled particles in an overdamped, flashing ratchet display higher center-of-mass velocity and energetic efficiency than a single particle [15]. Large collections of coupled particles in a flashing ratchet can undergo spontaneous oscillations [16], similar to the cooperative motion of muscle myosin.…”
Section: Introductionmentioning
confidence: 99%
“…One reason is that such studies may provide a route to models of the linear transport of biological molecular motors. A number of studies have demonstrated behavior of mechanically coupled particles which is qualitatively different than that of a single particle [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30], for example: In contrast to the behavior of an individual particle, two harmonically coupled particles in a flashing ratchet undergo directed motion in the absence of thermal fluctuations [12,13]. For a flashing ratchet, two harmonically coupled particles have a smaller velocity than a single particle, while for a rocking ratchet, the coupled particles have a greater velocity [14].…”
Section: Introductionmentioning
confidence: 99%
“…Brownian motors have attracted much attention as models of stochastic dynamical system [1,2], and their physical properties such as velocity, efficiency, diffusion coefficient [3][4][5][6], transport coherent [7,8] and temporal irregularity [9,10], have been studied during the past decades, and these models have been widely used to describe the motion or ✩ Fully documented templates are available in the elsarticle package on CTAN. transport behaviors of Brownian particles in both fundamental aspects of nonequilibrium statistical physics and various interdisciplinary applications, such as molecular motors [2], nanoscale friction [11,12] and surface smoothening [13].…”
Section: Introductionmentioning
confidence: 99%
“…Here, the coupled effects should be taken into account to study the phenomenon that the myosin filaments actively slide along the actin filaments together in large groups, driven by the chemical energy. Thus it is natural that some theoretical models of coupled system [6,[15][16][17] were proposed to describe and explain the cooperative behaviors of large ensembles of Brownian motors, which could lead to dynamical transition and instabilities, and then generated the collective directed transport phenomenon even if the system is symmetric. Meanwhile, except for the elastically coupled model, the investigation has been extended to the coupled Brownian motors with linear [6,[18][19][20][21], logarithmic [22] or global [23][24][25] couplings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation